Feasibility Study for Lithium Ion Battery Production in Uncertainty Situation - Shoushtari, Farzaneh; Li, Chang (International journal of industrial engineering and operational research, 2023)
The demand for energy storage systems, particularly lithium-ion batteries, has significantly increased due to their widespread use in various applications such as electric vehicles, renewable energy integration, and portable electronics. However, uncertainties surrounding lithium-ion batteries, including factors like price volatility, supply chain disruptions, and safety concerns, pose challenges to their feasibility. This paper aims to conduct a comprehensive feasibility study to assess the viability of lithium-ion batteries in uncertain situations. Through an investigation of the current literature, a methodology is proposed to evaluate the feasibility, followed by numerical results that highlight the potential advantages and disadvantages of utilizing lithium-ion batteries in uncertain scenarios. Finally, conclusions are drawn, providing insights into the practicality of lithium-ion batteries and suggesting avenues for further research.